Sevoflurane inhalation has a cognitive impairing effect of aging rats involving the regulation of AChE and ChAT. Issue 3 (28th September 2021) - Yang, Xin‐Xin; Wu, Zhen‐Yu; Yang, Yang; Zhang, Chao; Lin, Xia‐Fei; Zhou, Lin; Wang, Feng‐Lin; Dong, Liang; Zhu, Zhao‐Qiong
Abstract : Background: Acetylcholinesterase (AChE) and choline acetyltransferase (ChAT) are closely related to the regulation of learning and memory. Nevertheless, whether sevoflurane has influence on cognition through regulating the expression of AChE and ChAT remains unclear. Methods: Aging rat model was established by subcutaneously injection of D‐galactose for 6 consecutive weeks. To determine the role of AChE and ChAT in sevoflurane‐induced cognitive impairment, the Morris water maze (MWM) was used to assess the cognitive and memory function after sevoflurane exposure. Then, the variations of AChE and ChAT was detected by western blotting analysis and quantitative real‐time polymerase chain reaction (qRT‐PCR) respectively. Results: Our result indicated that aging model rats had showed cognition decline at 2 hours and 1week after exposure to sevoflurane. Moreover, the expression of AChE and ChAT enhanced in rats that had inhaled sevoflurane. Interestingly, our study also found that the increase of oxygen concentration had a positive impact on the gene expression of ChAT. Conclusion: We have identified that the overexpression of AChE and ChAT improved significantly cognitive function after sevoflurane exposure.